2012
DOI: 10.1093/jac/dks061
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporin-resistant Shigella flexneri over 9 years (2001-09) in India

Abstract: We report a high level of cephalosporin resistance with high MICs and ESBL- and AmpC-mediated antibiotic resistance in Shigella from north India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 30 publications
0
53
1
1
Order By: Relevance
“…The increasing levels of antimicrobial resistance of Shigella isolates have complicated the treatment of shigellosis. The antimicrobial resistance patterns of Shigella species differ according to geographic area and in the same place over time, leading to therapeutic problems (2,(18)(19)(20). Periodic regional monitoring of disease with serotype breakdown and regular periodic antibiotic-susceptibility testing patterns of isolates to guide local empirical therapy are important factors for the adequate control of shigellosis.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing levels of antimicrobial resistance of Shigella isolates have complicated the treatment of shigellosis. The antimicrobial resistance patterns of Shigella species differ according to geographic area and in the same place over time, leading to therapeutic problems (2,(18)(19)(20). Periodic regional monitoring of disease with serotype breakdown and regular periodic antibiotic-susceptibility testing patterns of isolates to guide local empirical therapy are important factors for the adequate control of shigellosis.…”
Section: Introductionmentioning
confidence: 99%
“…bla TEM was the most common β-lactamase gene followed by bla CTX-M-1 , which was found to be the most frequent type of cephalosporinase conferring resistance to third generation cephalosporins especially to cefotaxime. 6,11,27 Among the study isolates 22% and 7% were found to carry bla TEM and bla CTX-M-1 genes respectively. Similarly Taneja et al 6 reported bla CTX-M-1 (n=10) in S. flexneri isolates, thus indicating the consistent prevalence in India.…”
Section: Discussionmentioning
confidence: 94%
“…13 Ceftriaxone resistance was also observed by a multicentre study in eight Asian countries, among Shigella isolates. 6 Generally, ampicillin resistance was encoded by OXA type β-lactamases. Overall, in the current study, 41% of the isolates harbored bla OXA genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Multidrug resistance in Shigella spp is also found at high rate. 12 Therefore, investigation of new drugs and materials to face the emerging resistance is needed.…”
mentioning
confidence: 99%